Rancang Bangun Prototype Automatic Transfer Switch (ATS) Untuk Beban Kategori 2E Pada Puskesmas Rawat Inap Berbasis Mikrokontroller Atmega16 - Juli Mansen; Novery Lysbetti (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2016)
Generally, National Electrical Company (PLN) is main electrical energy supplier in Indonesia. Disturbances in the power system of PLN can occur anytime and make blackout on consumers. To support human activity, electrical energy from main source is expected to be available continuously. So, main power supplier must be equipped with alternative electrical energy providers such as generator. Aim of this research is to produce a prototype ATS category 2E controls switch movement based on microcontroller ATMega16. Based on PUIL 2000, blackouts are allowed on category 2E around <0.5 second. This problem can be solved by using UPS, because it is always standby. Priority orders of power system on this prototype are PLN and Generator. Parameters of PLN are voltage (198Volt-231Volt) and frequency (48Hz-52Hz). Generator parameter is voltage (198Volt-231Volt). When both PLN parameters are reached, the loads are supplied by PLN. When PLN is off or although one or both of PLN parameters achieved, ATS examines generator. If generator voltage is reached, loads are supplied by generator. If generator is off, ATS starts-up generator automatically, and loads supplied by UPS until generator be stable to supply the loads again. This research shows ATS can move switch successfully when parameters of the main source are not achieved. ATS also succeed to start-up generator automatically in 6.07 seconds when PLN suddenly off. The averages of transfer time on category 2E load occur are 2ms (PLN/Generator-UPS) and 7ms (PLN/Generator-UPS). They are smaller than PUIL standardization. This study has worked well as its framework.Keyword : Transfer Switch, Generator, PLN, UPS